Proposta de sequência didática para o ensino de fisiologia humana integrando os sistemas locomotor e nervoso - Silva, Ana Flávia Faverão Ferreira da (Universidade Federal de São Carlos, 2022)
The teaching of science and biology still faces several challenges to be overcome, especially in relation to the exacerbated number of existing concepts and the fragmentation of content dealt with in these disciplines. The area of Physiology, based on the high number of concepts and the present fragmentation of content, deserves special attention in order to overcome these challenges. Along with this, inside the schools, we still find many classes based on the traditional teaching model, even though we know that, based on our current society, it must also be overcome. Thus, this paper aims to propose a didactic sequence for the teaching of Human Physiology, based on the Dialogical Learning and the Three Pedagogical Moments (3MP). This theoretical and methodological foundation has pointed evidence to overcome these challenges, in order to move towards a more democratic and egalitarian education.
Didactic sequence proposal for human physiology teaching integrating the locomotor and nervous systems
Keywords: Aprendizagem dialógica; Três momentos pedagógicos; Ensino de biologia; Ensino de ciências; Science teaching; Biology teaching; Dialogical learning; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO